A Randomized, Multicenter, Double-Blind, Parallel Pilot Study Assessing the Effect of Mechanical Adhesiolysis vs Adhesiolysis with Corticosteroid and Hyaluronidase Administration into the Epidural Space During Epiduroscopy - Rapčan, Róbert; Kočan, Ladislav; Mláka, Juraj; Burianek, Miroslav; Kočanová, Hana; Rapčanová, Simona; Hess, Michael; Hammond, Anthony; Griger, Martin; Venglarčík, Michal; Gajdoš, Miroslav; Vašková, Janka (Pain medicine (Malden, Mass.), 2018)
OBJECTIVE: Epiduroscopy is a proven method of diagnosis and treatment for chronic radicular pain after spinal surgery, which is known as failed back surgery syndrome (FBSS). The aim of the study was to compare the efficacy of drugs (the enzyme hyaluronidase and corticosteroid DEPO-Medrol) administrated into the epidural space during epiduroscopy, performed within the ventral and ventro-lateral epidural space with a focus on releasing foraminal adhesions. METHODS: Forty-eight patients with diagnosed FBBS were randomized into two groups before epiduroscopy. Group A received the standard treatment-mechanical lysis of fibrotic tissue in the epidural space. Group B received hyaluronidase and corticosteroid methylprednisolone acetate during the procedure. Subjects were followed for six and 12 months via scheduled double-blinded examinations by pain physicians. Leg and back pain intensity was assessed by an 11-point numerical rating scale, and patients' functional disability was assessed by the Oswestry Disability Index (ODI). RESULTS: Study subjects showed a significant decrease in ODI score in both groups (P < 0.05). Significantly lower pain scores for leg pain (P < 0.05) and back pain (P < 0.05) were also recorded after the six-month follow-up. However, the one-year follow-up showed a return to the baseline ODI values of most monitored pain scores in both groups (P > 0.05). Improvement was only noted on the NRS for back pain at one-year follow-up (P < 0.05). CONCLUSIONS: A significant improvement of leg and back pain was found in both groups after six months. ODI was significantly improved only in group B in both the six- and 12-month intervals. Back pain at one-year follow-up was only improved in group B.
Keywords: dvojitá slepá metoda; methylprednisolon; Hyaluronoglucosaminidase; Double-Blind Method; Adhesiolysis; Back Pain; Methylprednisolone; Epidural Space; Failed Back Surgery Syndrome; adheze tkání; hyaluronoglukosaminidasa; neuroendoskopie; Humans; failed back surgery syndrom; Tissue Adhesions; pilotní projekty; Neuroendoscopy; Pilot Projects; epidurální prostor; Epiduroscopy; hormony kůry nadledvin; Adrenal Cortex Hormones; lidé; Hyaluronidase